A Woman of Valour: The Biography of Marie-Louise Bouchard Labelle - Lord, Kathleen (Labour / Le Travail, 2011)
The article reviews the book, "A Woman of Valour: The Biography of Marie-Louise Bouchard Labelle," by Claire Trépanier, with translation by Louise Matha.
Keywords: BOOKS -- Reviews; LABELLE, Marie-Louise Bouchard; Nonfiction; TREPANIER, Claire; WOMAN of Valour: The Biography of Marie-Louise Bouchard Labelle, A (Book)